DIURNAL VARIATIONS IN PHYSICO-CHEMICAL FACTORS AND ZOOPLANKTON IN THE SURFACE LAYERS OF THREE FRESHWATER FISH PONDS - Michael, R George (Indian Journal of Fisheries, 2011)
MANY aquatic organisms exhibit diurnal rhythms in their activities. Although factors such as light, temperature, food, sex and size have been attributed as probable causes for such behaviour of planktonic organisms, subsurface illumination for the 24-hour period has been found to be the most essential stimulus (Lagarigue, 1949; Wells, 1960). Earlier investigations on this aspect have been reviewed by Gushing (1951), Welch (1952), Motoda (1953) and Davis (1955). While more or less adequate information on the diurnal variations in freshwater impoundments of temperate regions is available, similar works in the tropics are very few, as recently pointed out by George (1961).